Kinerja Keuangan Melalui Nilai Perusahaan Sebagai Variabel Moderasi: Environmental, Social, dan Governance (ESG) Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Amelia Rizanti; Vivi Nila Sari; Putri Intan Permata Sari (P3M Politeknik Negeri Bengkalis, 2025)
This research aims to determine the influence of environment, social and governance on financial performance with company value as a moderating variable. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. The sampling technique used was purposive sampling and 17 companies were obtained as observations totaling 85 times. The analysis method used is moderated regression. Based on the simultaneous test results, the environment, social and governance do not have a significant effect on financial performance, whereas with the moderating variable, the results of the simultaneous test show that the environmental, social and governance have a significant effect on financial performance with company value as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023.